Envolvimento dos receptores P2X3 na hiperalgesia muscular : Involvement of P2X3 receptors in muscle hyperalgesia - Aquino, Bruna de Melo, 1987- (2018)
Orientador: Maria Cláudia Gonçalves de Oliveira Fusaro